2005
DOI: 10.1007/s10661-005-1605-9
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Deposition on Swiss Long-Term Forest Ecosystem Research (LWF) Plots

Abstract: Atmospheric deposition of the major elements was estimated from throughfall and bulk deposition measurements on 13 plots of the Swiss Long-Term Forest Ecosystem Research (LWF) between 1995 and 2001. Independent estimates of the wet and dry deposition of nitrogen (N) and sulfur (S) on these same plots were gained from combined simplified models. The highest deposition fluxes were measured at Novaggio (Southern Switzerland), exposed to heavy air pollution originating from the Po Plain, with throughfall fluxes av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 31 publications
2
70
0
Order By: Relevance
“…The simple extrapolation method by weighting by the number of days resulted in somewhat lower but on the whole similar fluxes (Table 2) -N estimated in this study were within the range of typical values for temperate European beech forests (e.g., Berger et al 2009b;Thimonier et al 2005). Even though our estimated throughfall flux of Ca 2+ was rather low in comparison to other findings in the literature, Berger et al (2009b) found similar low values.…”
Section: Estimation Of Annual Fluxessupporting
confidence: 84%
See 2 more Smart Citations
“…The simple extrapolation method by weighting by the number of days resulted in somewhat lower but on the whole similar fluxes (Table 2) -N estimated in this study were within the range of typical values for temperate European beech forests (e.g., Berger et al 2009b;Thimonier et al 2005). Even though our estimated throughfall flux of Ca 2+ was rather low in comparison to other findings in the literature, Berger et al (2009b) found similar low values.…”
Section: Estimation Of Annual Fluxessupporting
confidence: 84%
“…The lower N fluxes in throughfall compared to bulk precipitation also indicate that dry deposition of inorganic N compounds on foliage, in the form of gases or aerosols, is probably quite low in our study site. In many European temperate broadleaved forests, throughfall fluxes exceed bulk precipitation fluxes due to the wash-off of dry-deposited compounds (e.g., Kristensen et al 2004;Thimonier et al 2005), even though N is most likely taken up by the canopy as well (Harrison et al 2000). The strongly enhanced throughfall K + concentrations and fluxes that we observed at our beech stands is also well documented in the literature for tree canopies (Stachurski and Zimka 2002).…”
Section: General Effect Of the Tree Canopy On Precipitation Chemistrysupporting
confidence: 83%
See 1 more Smart Citation
“…This study was carried out on five well characterized forest soils (Beatenberg, Lausanne, Novaggio, Schänis, Vordemwald) of the Swiss long-term forest ecosystem research programme (LWF) that were selected due to their geographical location, soil properties and available data sets (Graf-Pannatier et al, 2011;Heim and Frey, 2004;Thimonier et al, 2005;Walthert, 2003). All soils were from natural forest sites distributed over the different geographical regions in Switzerland.…”
Section: Sites Descriptionmentioning
confidence: 99%
“…The soil depths and main properties of L1 and L2 are given for each soil site in Table 1. Annual average precipitation data, data of total and wet deposition (for cations, N and S) have been determined on these five LWF sites with continuous sampling of bulk (1 to 3 samplers in a nearby open field) and throughfall deposition (4 to 16 samplers below forest canopy) in bi-weekly to monthly intervals since 1997 (Thimonier et al, 2010;Thimonier et al, 2005). In the few cases with overflow of the samplers, precipitation has been reconstructed using data of unheated tipping buckets or of the nearest meteorological station of the Swiss meteorological institute MeteoSwiss.…”
Section: Input Datamentioning
confidence: 99%